Historical encyclopedia of nursing - Snodgrass, Mary Ellen (Santa Barbara, Calif. : ABC-CLIO, 1999)
An encyclopedia covering the history of nursing, spanning topics from abortion to World War II.
Includes bibliographical references (p. 315-333) and index.
Keywords: Nursing -- History -- Encyclopedias; Nursing -- History -- Encyclopedias